Application of Lattice Boltzmann Method to Simulate Forest Edge (Advances in Applied Mathematics and Mechanics, 2022)
This study is focused on the forest edge flow by using numerical method.To model the effects of a forest canopy on airflow, source terms are introduced into thegoverning equations. The lattice Boltzmann method in conjunction with the standard $k−ε$ model is applied to solve the turbulent wind field. In order to perform the simulation on non-uniform grids, the Taylor series expansion and least square based latticeBoltzmann method (TLLBM) is adopted to improve the accuracy and computationalefficiency. The present method and code are verified with an earlier forest edge simulation. A series of forest canopies are established to explore the impacts of canopy morphology on wind field. These canopies cover 3 canopy architectures and the Leaf AreaIndex (LAI) ranges from 2.0 to 4.0. The further study is carried out by adjusting thecanopy foliage amount and the canopy architecture. The present study demonstratesthe potential of lattice Boltzmann method to simulate the high Re number forest edgeflow. The impacts of canopy morphology on zero plane displacement, aerodynamicroughness length, friction wind velocity, permeability coefficient, wall-shear stress areillustrated in detail. The results show that the canopy sub-layer wind field, especiallythe wind velocity profiles within and above the forest canopy, are mainly determinedby canopy morphology.